Righteous Strife: How Warring Religious Nationalists Forged Lincoln's Union. By Richard Carwardine. New York: Alfred A. Knopf, 2025. xxiv + 598 pp. 19.95 paper - Byrd, James P. (Church history, 2025)
Righteous Strife: How Warring Religious Nationalists Forged Lincoln's Union. By Richard Carwardine. New York: Alfred A. Knopf, 2025. xxiv + 598 pp. 19.95 paper. - Volume 94 Issue 2